Use of Cooperative Learning Model With Team Games Tournament (TGT) to Increase Students’ Learning Achievement in Islamic Education at SMAN 6 Wangi-Wangi of Wakatobi - Samrin Samrin; Mohammad Rijal; Syamsuddin Syamsuddin (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This classroom action research (CAR) aims to improve the students’ learning achievement in Islamic Education through a cooperative model with Teams Games Tournament (TGT). Data collection is conducted at SMAN 6 Wangi-Wangi at class XB through observation, tests, and documentation. This research is conducted in two cycles. The results indicate that the implementation of TGT to students of class XB at SMAN 6 Wangi-Wangi significantly improve the students’ Islamic education learning achievement. This judgement is based on the preliminary test results carried out before the cycle 1, stating that fourteen students (56%) reached 73 as their score with an average score of 72.28. After the cycle 1, nineteen students (76%) reached standard score (KKM) for this subject with an average score of 79.96. However, this result has not been considered as successful students because their score has not met the success indicator of 80, accordingly cycle 2 was conducted. Cycle 2 indicates that 22 students (88%) have reached beyond the standard score with an average score of 85.04. This result implies that TGT can significantly improve the students’ learning achievement in Islamic education at class XB of SMAN 6 Wangi-Wangi, Wakatobi.